The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/polym13060890
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Treatment with Isocyanate and Aromatic Carbodiimide of Thermally Expanded Vermiculite Used as a Functional Filler for Polylactide-Based Composites

Abstract: In this work, thermally expanded vermiculite (TE-VMT) was surface modified and used as a filler for composites with a polylactide (PLA) matrix. Modification of vermiculite was realized by simultaneous ball milling with the presence of two PLA chain extenders, aromatic carbodiimide (KI), and 4,4’-methylenebis(phenyl isocyanate) (MDI). In addition to analyzing the particle size of the filler subjected to processing, the efficiency of mechanochemical modification was evaluated by Fourier transform infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Bending vibrations of these bands were expressed by the signals around 450 cm −1 . They were more pronounced for the composites filled with vermiculite, which is in line with our previous studies, indicating a powerful absorption band around 1000 cm −1 [26].…”
Section: Structural Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Bending vibrations of these bands were expressed by the signals around 450 cm −1 . They were more pronounced for the composites filled with vermiculite, which is in line with our previous studies, indicating a powerful absorption band around 1000 cm −1 [26].…”
Section: Structural Analysissupporting
confidence: 92%
“…Before use, VM was subjected to milling with the knife mill Retsch GM200 with a knife rotational speed of 5000 rpm and 5 min, and was sieved by a Fritsch Analysette 3 mechanical siever using 100 µm mesh. The annealing process was carried out at a temperature of 1260 • C, and the chemical composition according to the manufacturer's data is 38.0-49.0% SiO 2 , 20.0-23.5% MgO, 12.0-17.5% Al 2 O 3 , 0.3-5.4% Fe 2 O 3 , 5.2-7.9% K 2 O, 0.0-1.2% FeO, 0.7-1.5% CaO, 0.0-0.8% Na 2 O, 0.0-1.5% TiO 2 , 0.0-0.5 Cr 2 O 3 , 0.1-0.3% MnO, 0.0-0.6% Cl, 0.0-0.6% CO 2 , 0.0-0.2% S. Broader information about the used fillers was presented in a previous works [25][26][27].…”
Section: Methodsmentioning
confidence: 94%
“…Glass transition temperature (T g ), cold crystallization temperature (T cc ), and melting temperature (T m ) were determined for all biocomposites using DSC analysis. The crystallinity of the samples (X c ) was calculated according to the following Equation (2) [ 2 , 53 , 54 ]: where is a cold crystallization enthalpy; is a melting enthalpy; is a melting enthalpy of fully crystalline PLA, which is 93.6 J/g [ 55 ], and is a weight fraction of PLA in the biocomposites ( Table 4 ) or in neat PLA. Table 10 and Figure 8 show the results of DSC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that PLA, the polymer matrix employed in this FDM process, has a deflection temperature (HDT) near 55 • C [52,53]. HDT is a measure of the resistance of a polymer to deformation (stiffness of material) when subjected to stress loading at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%